Decomposição de argilas em forno de microondas e determinação simultânea dos seus constituintes principais por espectrometria de emissão óptica em plasma indutivamente acoplado - Silva, C. R.; Nobrega, J. A.; Blanco, T. (Soc Brasileira Quimica, 2005)
ANALYSIS OF CLAYS BY INDUCTIVELY COUPLED PLASMA OPTICAL EMISSION SPECTROMETRY AFTER CLOSED-VESSEL MICROWAVE-ASSISTED ACID DECOMPOSITION. In this work a closed-vessel microwave-assisted acid decomposition procedure for clays was developed. Aluminum, Ca, Fe, K, Mg, Na, Si, and Ti were determined in clay digestates by inductively coupled plasma optical emission spectrometry. The most critical parameter for total decomposition of clays was the composition of the reagent mixture. The applied power and the heating time exerted a less critical influence. Best decomposition conditions were attained using a reagent mixture containing 4 mL aqua regia plus 3 mL HF and the heating program was implemented in 12 min. The accuracy of the results was demonstrated using two standard reference materials and a paired t-test showed a good agreement between determined and certified values at a 95% confidence level.
Analysis of clays by inductively coupled plasma optical emission spectrometry after closed-vessel microwave-assisted acid decomposition.
Keywords: clays; microwave-assisted decomposition; ICPOES